Improved parental understanding by an enhanced informed consent form: a randomized controlled study nested in a paediatric drug trial - Nut Koonrungsesomboon; Chanchai Traivaree; Charnunnut Tiyapsane; Juntra Karbwang (BMJ Open)
Objective This study was designed to evaluate the applicability and effectiveness of the enhanced informed consent form (ICF) methodology, proposed by the Strategic Initiative for Developing Capacity in Ethical Review (SIDCER), in paediatric research requiring parental consent. The objective of this study was to compare the parental understanding of information between the parents who read the SIDCER ICF and those who read the conventional ICF.Design A prospective, randomized, controlled design.Setting Paediatric Outpatients Department, Phramongkutklao Hospital, Thailand.Participants 210 parents of children with thalassemia (age=35.6 ± 13.1 years).Interventions The parents were randomly assigned to read either the SIDCER ICF (n=105) or the conventional ICF (n=105) of a paediatric drug trial.Primary and secondary outcome measures Parental understanding of trial information was determined using 24 scenario-based questions. The primary endpoint was the proportion of parents who obtained the understanding score of more than 80%, and the secondary endpoint was the total score.Results Forty-five parents (42.9%) in the SIDCER ICF group and 29 parents (27.6%) in the conventional ICF group achieved the primary endpoint (relative risk=1.552, 95% CI 1.061 to 2.270, p=0.021). The total score of the parents in the SIDCER ICF group was significantly higher than the conventional ICF group (18.07±3.71 vs 15.98±4.56, p=0.001).Conclusions The SIDCER ICF was found to be superior to the conventional ICF in improving parental understanding of trial information.